Analisis Resiko Terkait Kecelakaan Kerja di Tambang Batubara dan Faktor Risiko Terkait - Aisah Amini; Susilawati, Susilawati (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Mining operations need to recognize potential hazards, evaluate the risks involved, and continuously control risk to a manageable level. In addition to statistical data, other factors contributing to the rise in industrial accidents in businesses include the effective tunnel temperature, which is between 27 and 29 °C, hazardous mine gases, employee neglect of personal protective equipment, and a lack of hazard awareness in some workplaces. Based on these issues, the study's objectives are to illustrate how corporate OSH is used, provide data on work accidents and potential risk factors in the workplace, and make recommendations for a number of work practice guidelines. The world's most hazardous occupation is mining. the Ministry of Energy and Mineral Resources' statistical data. In mining, accidents frequently happen. Hazardous field conditions, unsafe work practices, and a disregard for safety are the root causes of dangerous working circumstances. As a result, fatal work accidents frequently happen. In order for businesses and employees to reduce the risk of work accidents, this research's goal is to identify the factors that lead to accidents at work in the coal mining industry. Data sources for this study were gathered from "Google Scholar" using the keywords "The year of publication is limited to 2018–2022." This study used the systematic literature review (SLR) technique. Risk variables are the most crucial elements employed in preventing work accidents, according to a study of the literature on how age, job experience, the workplace, and body parts affect employee work accidents., and the role of the company in influencing the occurrence of accidents. work accident.